Program Membangun Pembelajaran Islami dengan Memanfaatkan Momentum Bulan Ramadhan di Trensami Kwangsan Sedati Sidoarjo - Denis Nurista Sari (Jurnal Pengabdian Masyarakat, 2026)
The Community Service Activity titled “Building Islamic Learning by Capitalizing on the Momentum of Ramadan” aims to enhance participants’ understanding of the importance of integrating Islamic values into the learning process. The month of Ramadan holds great potential as an educational opportunity that emphasizes not only academic aspects but also the strengthening of students’ character, spirituality, and moral values. This activity was conducted in the form of a webinar involving students, teachers, and learners as the target audience. The method used in this activity was Participatory Action Research (PAR), which emphasizes active participant involvement in every stage of the activity, from planning and implementation to reflection. The activity was carried out in several stages, namely participant orientation, presentation of material by resource persons, discussion and Q&A sessions, as well as documentation and closing of the activity, which concluded with a communal iftar. The results of the activity showed that participants demonstrated high enthusiasm throughout the event and gained a better understanding of the application of Islamic learning through Ramadan activities such as Quran recitation, congregational prayer, and religious social activities. It is hoped that this activity will encourage educators to utilize the momentum of Ramadan as a means of more contextual, religious, and meaningful learning in character building.